Forme ale discriminării împotriva cerșetorilor și persoanelor fără adăpost - Adrian Toma; Geanina-Ștefana Moțățeanu (Drepturile Omului)
This paper presents an argument for the necessity of intervention in marginalized areas of society, where individuals encounter discrimination, social exclusion, and stigmatization. As a result, they are unable to exercise the rights guaranteed by the Romanian Constitution. The underlying causes of this situation stem either from the socially conditioned deterioration of the individuals’ personal circumstances to a degree that prevents them from exercising their rights, or from the severe challenges posed by their environment – such as for beggars or homeless individuals – where the state’s institutions fail to ensure the minimum conditions required for survival. The research focuses on thirty-two fundamental rights and freedoms enshrined in the Romanian Constitution, examining how these rights are realized in the interactions between the most impoverished members of society and various state institutions, such as: law enforcement agencies, social workers, medical personnel, tax authorities, local public administration entities, as well as the business sector and host communities. The study finds that, in the case of twenty-three of these fundamental freedoms, there are significant limitations on the exercise of human rights.